2023
DOI: 10.1186/s13741-023-00316-0
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between fear of surgery and affecting factors in surgical patients

Abstract: Background This study aimed to explain the fear of surgery in surgical patients, the affecting factors, and their relationship. Methods This study was conducted as a descriptive and cross-sectional study. The study population consists of 300 patients undergoing surgical intervention. Data were collected using the “patient information form” and “Surgical Fear Questionnaire.” Parametric and nonparametric tests were used to evaluate the data. The rela… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…12 By contrast, other research findings in the literature report that geriatric patients have a lower fear of surgery. 9,25 Research has reported that age and surgery-specific anxiety are positively related, 26,27 but in others studies, age and anxiety level are found to be negatively related. 28,29 Furthermore, Rosiek et al found no relationship between the level of surgery-specific anxiety and age.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…12 By contrast, other research findings in the literature report that geriatric patients have a lower fear of surgery. 9,25 Research has reported that age and surgery-specific anxiety are positively related, 26,27 but in others studies, age and anxiety level are found to be negatively related. 28,29 Furthermore, Rosiek et al found no relationship between the level of surgery-specific anxiety and age.…”
Section: Discussionmentioning
confidence: 95%
“…There are studies in the literature in which the mean fear and anxiety scores of female patients are higher than those of males. 9,25,30,[32][33][34] Anxiety disorders are the most common psychological disorders in societies. According to the data of the American National Comorbidity Study, the lifetime prevalence rates are 30.5% in women and 19.2% in men, 35 so it may be speculated that mutually triggering biological and psychosocial factors cause an increase in anxiety and fear levels in females.…”
Section: Discussionmentioning
confidence: 99%
“…A preliminary study conducted among 65 patients awaiting cardiac surgery provided promising results regarding the reliability of the scale (Cronbach's a coefficient for the full scale was 0.93, for short-term aspects of surgery was 0.91, and for long-term surgery aspects was 0.90). The SFQ questionnaire has been used in studies conducted in the Netherlands [28,29], Greece [34], Portugal [35,36], Turkey [21,23,33,[37][38][39][40][41][42][43], Croatia [44], Norway [45], Germany [31], Italy [46], Czech Republic [30], China [32], United States [47,48], Ireland [49], and Hungary [50][51][52]. Most of these publications appeared in the years 2022-2023.…”
Section: Prospective Evaluation Monitoring the Level Of Anxietymentioning
confidence: 99%
“…Studies have shown that 60-80% of individuals experience preoperative anxiety, significantly affecting postoperative aspects such as wound healing, pain control, anesthesia efficacy, and analgesia needs. Additionally, a patient’s emotional state before surgery can influence their physical and psychological recovery afterward [ 6 ]. New findings emphasize the significant influence of psychological factors on surgical outcomes, spanning both immediate and lasting effects [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is essential to pinpoint the factors contributing to fear and anxiety and uncover their relationships. This understanding is vital for crafting personalized interventions to improve surgical experience and postoperative healing [ 6 ].…”
Section: Introductionmentioning
confidence: 99%